2006
DOI: 10.1002/psc.775
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity relationship studies on the antimicrobial activity of novel edeine A and D analogues

Abstract: Edeines are pentapeptide amide antibiotics composed of four nonprotein amino acids, glycine, and polyamine. They exhibit antimicrobial and immunosuppressive activities and are universal inhibitors of translation. Moreover, it was proven that the free ionizable carboxy group in the (2R, 6S, 7R)-2,6-diamino-7-hydroxyazelaic acid moiety is not essential for biological activity of these compounds. In this paper we describe the synthesis of four novel edeine A and D analogues in which the above-mentioned acid resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…It was previously demonstrated that the presence of the free ionizable carboxyl group in the (2R,6S,7R)-A 2 ha moiety was not essential for the biological activity of edeines [20,21]. As a continuation of our research project [22], we recently synthesized the following edeine antibiotic analogues ( Compounds 1-4 were shown to exhibit significantly diminished antibacterial and antifungal activities [22], and they did not display toxic effects towards mammalian cells [23]. Initial studies on the immunological effect of edeine, performed in the mid seventies [9,11] demonstrated their suppressive actions in the models of the humoral and cellular immune responses of mice in vivo.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…It was previously demonstrated that the presence of the free ionizable carboxyl group in the (2R,6S,7R)-A 2 ha moiety was not essential for the biological activity of edeines [20,21]. As a continuation of our research project [22], we recently synthesized the following edeine antibiotic analogues ( Compounds 1-4 were shown to exhibit significantly diminished antibacterial and antifungal activities [22], and they did not display toxic effects towards mammalian cells [23]. Initial studies on the immunological effect of edeine, performed in the mid seventies [9,11] demonstrated their suppressive actions in the models of the humoral and cellular immune responses of mice in vivo.…”
Section: Introductionmentioning
confidence: 66%
“…That effect could be due to the direct binding of LPS by highly basic edeine molecules. It is also evident that the substantial decrease in the antibacterial and antifungal activity [22] correlated with the acquisition of interesting immunomodulatory properties (this article). In conclusion, some of the peptides deserve further studies in other experimental models, which could reveal potential therapeutic benefit.…”
Section: Cellular and Molecular Biology Letters 159mentioning
confidence: 81%
See 1 more Smart Citation
“…Note that some peptides can show more than one activity. For example, there are 9 curated peptides in the Norine database that present both antibiotic and immunomodulator activities (such as edeines [12]) and 14 didemnins (66) that present three activities, antibiotic, antitumor, and immunomodulator.…”
Section: Study Of Biological Activity (I) Statistical Resultsmentioning
confidence: 99%
“…It can secrete large amounts of secondary metabolites, which are important for controlling pathogens. Among them, tyrocidine, gramicidin (4,5,6), gratisin (12), and edeine (1) have been successively isolated and identified. Only recently, the genome of one B. brevis strain, NBRC 100599, is available in the GenBank database (http://www .ncbi.nlm.nih.gov/nuccore/226309587?reportϭGenBank).…”
mentioning
confidence: 99%